Виды рода Telenomus Halidау, 1833 (Hymenoptera, Scelionidae) с укороченными крыльями - Козлов, М.А.; Кононова, С.В. (Вестник зоологии, 1978)
Two new for science species of Telenomus are described: T. flaviventris Kozlov et Kononova sp. n. and T. asperus Kozlov et Kononova, sp. n. Their characteristic feature is shortened wings.